Estimation of the carrying capacity in some Tuscan woods grazed by Cinta Senese pig - Acciaioli A.; Pianaccioli L.; Campodoni G.; Franci O. (5. International Symposium on the Mediterranean Pig, 2007)
In Tuscany, pig grazing in the woods shows new perspectives compared to the past, because of differences in rearing systems and wood structure. To exploit wood resources in a sustainable way it is necessary to define the carrying capacity by determining its productivity and acorn nutritive value. An in vivo digestibility trial on acorn, compared to barley, was carried out using 12 pigs (6 Cinta Senese and 6 Large White). Acorn productivity of Turkey-oak (Quercus cerris) and Holm-oak (Quercus ilex) wood was employed.Wood production in both areas was highly variable and holm-oak was more productive than turkey-oak. DE content of acorn (5.5 MJ/kg of feed) was similar in the two species. Estimated carrying capacity of holm-oak wood varied from 0.4 to 3.5 fattening pigs/ha over a period of 150 days. The carrying capacity of turkey-oak wood varied from 0.1 to 2.1 pigs/ha over a period of 90 days. Reliable estimates of the carrying capacity of woods are recommended to avoid damage to the ecosystem.
5. International Symposium on the Mediterranean Pig, 2004/09/16-19, Tarbes (France)